2013
DOI: 10.1111/cas.12292
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin, an NADPH oxidase inhibitor, suppresses rat prostate carcinogenesis

Abstract: Recent evidence suggests that oxidative stress contributes to the pathogenesis of prostate cancer. The present study focused on the effect of apocynin, an inhibitor of NADPH oxidase, on prostate carcinogenesis using the transgenic rat for adenocarcinoma of prostate (TRAP) model. There were no toxic effects with apocynin treatment. The percentages and numbers of carcinomas in both the ventral and lateral prostate were significantly reduced by apocynin treatment, with dose dependence. Reduction of reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…It has been reported that Nox1 knockdown induces G 0 /G 1 arrest in a human colon cell line, HT29, whereas the same knockdown treatment in Caco2 cells strongly induces apoptosis . In addition, apocynin also blocks cell growth by inducing G 0 /G 1 arrest and downregulating cyclin D1 in a human prostate cancer cell line, LNCaP . We obtained similar results, showing that apocynin suppressed c‐Myc and cyclin D1 mRNA levels and reduced the ratio of PCNA‐positive epithelial cells in the intestinal polyp sections of Min mice.…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that Nox1 knockdown induces G 0 /G 1 arrest in a human colon cell line, HT29, whereas the same knockdown treatment in Caco2 cells strongly induces apoptosis . In addition, apocynin also blocks cell growth by inducing G 0 /G 1 arrest and downregulating cyclin D1 in a human prostate cancer cell line, LNCaP . We obtained similar results, showing that apocynin suppressed c‐Myc and cyclin D1 mRNA levels and reduced the ratio of PCNA‐positive epithelial cells in the intestinal polyp sections of Min mice.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have shown that mitogen-activated protein kinases (MAPKs) became inactivated after the treatment of cancer cells with chemopreventive agents, such as angiotensin II receptor blocker, purple corn color or apocynin [16,17,18]. To elucidate the mechanisms of anti-carcinogenesis by PGZ, we therefore investigated the activation of p38 MAPK and ERK1/2 in prostate tissues of TRAP rats.…”
Section: Resultsmentioning
confidence: 99%
“…Neoplastic lesions in the prostate gland of TRAP rats were evaluated as previously described [17,18,30]. Briefly, neoplastic lesions were classified into three types: LG-PIN, HG-PIN and adenocarcinoma.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio and numbers of carcinomas in prostates were significantly reduced by apocynin treatment, with dose dependence (Suzuki et al 2013a). The ratio and numbers of carcinomas in prostates were significantly reduced by apocynin treatment, with dose dependence (Suzuki et al 2013a).…”
Section: Apocynin (4 0 -Hydroxy-3 0 -Methoxyacetophenone; Acetovanillmentioning
confidence: 97%